Coriander production system in Puebla and its impact on safety - Tibaduiza-Roa, Verónica; Huerta-de la Peña, Arturo; Morales-Jiménez, Juan; Hernández-Anguiano, Ana María; Muñiz-Reyes, Érica (Revista Mexicana de Ciencias Agrícolas, 2018)
Coriander (Coriandrum sativum L.) is one of the main vegetables produced in the municipality of The Reyes of Juarez Puebla. However, this crop has been subject to health warnings due to outbreaks of cyclosporiasis in the USA due to the consumption of Coriander from Puebla. Recognizing its economic importance and the need to improve the production system, this work aimed to register current agricultural practices in coriander production and analyze its impact on product safety to identify opportunities for improvement. From an official list, a simple random sampling and maximum variance 73 (n) producers were selected to whom a questionnaire was applied to gather information on the activities they implement during crop production. Field visits were made in the period from January to September to make ocular observations of said activities. The results indicated that the current production system has a strong impact not only on the safety of the product but also on the health of the people involved in the agricultural activities of the crop, which requires the implementation of pollution prevention programs.
Keywords: Coriandrum sativum; hygiene; risks; health